Intervención y promoción sobre prácticas de lactancia materna exclusiva a puerperas que acuden al Centro de Salud Montalvo. octubre 2018 - abril 2019 - Zambrano Benavides, Jennifer Valeria (2019)
Introduction. For millennia, breast milk has been the most nutritious and effective source of nutrition for infants. It must be provided as the only food until the child's six months of life because it contributes to their physical, intellectual and social development and favors the saving of economic resources at the family level. General objective. Describe the interventions and promotional activities on exclusive breastfeeding practices for puerperal women who come to the Montalvo Health Center in Los Ríos province in the period from October 2018 to April 2019 Methodology. Qualitative-quantitative field research, exploratory and descriptive, applied and non-experimental, cross-sectional. Information gathering techniques were used as unscientific scientific observation, direct and survey; A questionnaire was applied as an instrument. The sample of 40 puerperal women who attended the Montalvo Health Center, sampling was intentional non-probabilistic. Results. Adolescents (25%), secondary level (50%), housewives (45%), in free union (42.5%), who provide mixed breastfeeding (80%), with support from the family (65%), they abandon exclusive breastfeeding because they are not full (32.5%), they have received information about breastfeeding techniques in 77.5%, they know the benefits and techniques of the LME, they identify and fulfill the nursing interventions on the practice of exclusive breastfeeding in more than half. Conclusions. The interventions were identified, offer education about the correct breastfeeding technique, inform about the benefits of exclusive breastfeeding and its peculiarities, offer education about breast milk extraction and storage techniques and the adapted formula, orient the maternal and child bond and offer information on how to develop a practical exercise of expressing breast milk.